Inhibition of regrowth of planktonic and biofilm bacteria after peracetic acid disinfection. (1st February 2019) - Zhang, Chiqian; Brown, Pamela J.B.; Miles, Randall J.; White, Tommi A.; Grant, DeAna G.; Stalla, David; Hu, Zhiqiang
Abstract: Peracetic acid (PAA) is a promising alternative to chlorine for disinfection; however, bacterial regrowth after PAA disinfection is poorly understood. This study compared the regrowth of bacteria (Gram-negative Pseudomonas aeruginosa PAO1 and Gram-positive Bacillus sp.) after disinfection with PAA or free chlorine. In the absence of organic matter, PAA and free chlorine prevented the regrowth of planktonic cells of P. aeruginosa PAO1 at C·t (= disinfectant concentration × contact time) doses of (28.5 ± 9.8) mg PAA·min·L −1 and (22.5 ± 10.6) mg Cl2 ·min·L −1, respectively, suggesting that they had comparable efficiencies in preventing the regrowth of planktonic bacteria. For comparison, the minimum C·t doses of PAA and free chlorine to prevent the regrowth of P. aeruginosa PAO1 biofilm cells in the absence of organic matter were (14, 000 ± 1, 732) mg PAA·min·L −1 and (6, 500 ± 2, 291) mg Cl2 ·min·L −1, respectively. PAA was less effective than free chlorine in killing bacteria within biofilms in the absence of organic matter most likely because PAA reacts with biofilm matrix constituents slower than free chlorine. In the presence of organic matter, although the bactericidal efficiencies of both disinfectants significantly decreased, PAA was less affected due to its slower reaction with organic matter and/or slower self-decomposition. For instance, in a dilute Lysogeny broth-Miller, the minimum concentrations of PAA and free chlorine to prevent the regrowth of planktonic P. aeruginosa PAO1 were 20 mg PAA·L −1 and 300 mg Cl2 ·L −1, respectively. While both disinfectants are strong oxidants disrupting cell membrane, environmental scanning electron microscopy (ESEM) revealed that PAA made holes in the center of the cells, whereas free chlorine desiccated the cells. Overall, this study shows that PAA is a powerful disinfectant to prevent bacterial regrowth even in the presence of organic matter. Graphical abstract: Image 1 Highlights: PAA and chlorine effectively killed planktonic cells in the absence of organic matter (OM). PAA was less effective than chlorine in preventing cell regrowth after biofilm treatment in the absence of OM. PAA was more effective than chlorine in preventing cell regrowth in the presence of OM. PAA disinfection was less affected by OM compared with chlorination. PAA caused holes to form in the center of cells, whereas chlorine desiccated the bacteria.